Experimental validation of two voltage regulation strategies for boost converters in wind systems - Imodane, Belkasem; Benydir, Mohamed; Bouachrine, Brahim; Ajaamoum, Mohamed; Dahmane, Kaoutar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This study provides an experimental validation of two advanced control methods, sliding mode control (SMC) and fuzzy logic control (FLC) for regulating the DC bus voltage in a permanent magnet synchronous generator (PMSG) wind turbine system using a boost converter. Initially, MATLAB/Simulink simulations are used to assess the system's behavior in an ideal environment, where various operating conditions and disturbances are modeled to test the robustness of the control algorithms. Subsequently, real experiments are conducted using a physical prototype of a boost converter and a LAUNCHXL-F28069M DSP board to evaluate the system's behavior under real-world scenarios. The evaluation focuses on system stability, tracking accuracy, and response time under various wind turbine operating conditions. The experimental results reveal that SMC outperforms FLC in terms of rapidity, precision, and hardware implementation. Additionally, SMC offers significant advantages in achieving superior performance metrics, such as improved dynamic response and enhanced overall system stability, making it a more effective choice for practical wind energy applications. This experimental validation simplifies the selection of optimal control strategies for wind energy systems.